Keragaman Morfologi, Genetika, dan Patogenisitas Colletotrichum acutatum PenyebabAntraknosa Cabai di Jawa dan Sumatera - Ibrahim, Roy; Hidayat, Sri Hendrastuti; widodo, widodo (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2017)
Colletotrichum acutatum is known as the major causal agents of anthracnose disease of chilli pepper in Indonesia. This research was aimed to study genetic variability of C. acutatum in Java and Sumatera based on morphological and molecular characteristics and to evaluate pathogenicity of several isolates. Observation on morphological characteristics involved colour and growth of each colony as well as shape and size of conidia. Molecular identification was performed by DNA amplification using specific primer for C. acutatum, i.e. CaInt2/ITS4 followed by sequencing and nucleotide sequence analysis. Pathogenicity test for each isolate on Capsicum annuum and C. frutescens was conducted in the laboratory using detached chilli. Morphology variability was observed from 40 isolates of C. acutatum. Most of the isolates have white/beige colonies with fusiform conidia of 6.11–9.73 µm in length and 2.24–2.73 µm in width. Pathogenicity of 3 C. acutatum isolates varies from moderate to high based on lesions size on infected chilli. Sequence analysis of 8 C. acutatum isolates indicated high homology among isolates from Java and Sumatera